Benefits in Speech Recognition in Noise with Remote Wireless Microphones in Group Settings - Thibodeau, Linda M. (J Am Acad Audiol, 2020)
BACKGROUND: Although hearing aids (HAs) and cochlear implants (CIs) can provide significant benefits to persons with hearing loss, users frequently report difficulty hearing in noisy environments, particularly when there are multiple talkers. Little is known about the benefits provided by currently available wireless microphones in multitalker situations. PURPOSE: The purpose of this study was to compare the benefits received in speech recognition in noise by adults with hearing loss when using two different wireless microphone types in a simulated group setting. RESEARCH DESIGN: A quasi-experimental, repeated-measures design was used where performance in a control condition, HA/CI alone, was compared with performance in two wireless microphone intervention conditions. STUDY SAMPLE: Participants included ten listeners, aged 20–92 years, with bilateral sensorineural hearing loss who were experienced HA or CI users. INTERVENTION: The two wireless microphones by Phonak, Roger Pen, and Roger Select used the same digital modulation protocol to transmit the signal to compatible receivers. However, the Roger Pen operated in a fixed omnidirectional mode, whereas the Roger Select operated in an adaptive directional mode. DATA COLLECTION AND ANALYSIS: Participants were asked to repeat Hearing in Noise Test sentences presented in restaurant noise in three conditions: HA/CI alone, HA/CI with a Roger Pen, or HA/CI with a Roger Select microphone placed in the center of a round table. Sentences were presented from one of five loudspeakers equally spaced with the participant, while restaurant noise was presented on each side at four signal-to-noise ratios (SNRs), including +5, 0, −5, and −10 dB. A two-way, repeated-measures analysis of variance was performed with main effects of listening condition and noise level. RESULTS: Significantly greater speech recognition performance was achieved with the wireless microphones than with listening with just the HA or CI. Furthermore, at the −5- and −10-dB SNR conditions, the Roger Select resulted in significantly better performance than the Roger Pen microphone. CONCLUSIONS: The results suggest that the Roger Select microphone can provide significant benefits in speech recognition in noise over the use of HA/CI alone (61%) and also significant benefits over the use of a Roger Pen (16%) in a simulated group dining experience.